Prof. Abye Tasse (Ethiopia), President 2004-2008 - Karen Lyons (Social Work & Society, 2008)
It seems strange to be writing a biography of a man who is still very much alive and to be attempting some evaluation of his role in relation to IASSW when he does not formally conclude his Presidency until July 2008. However, apart from my own acquaintance with Tasse Abye through work in the European region for over a decade, and more recent contact with him and his family in Ethiopia, it has also been possible to interview him very recently; to draw on information from his CV; and to seek out views from colleagues who have also had the opportunity of working with him in various capacities in the more recent past.